2002
DOI: 10.1161/01.cir.0000018125.31973.87
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Syncope in Patients With Heart Disease and Negative Electrophysiologic Test

Abstract: on behalf of the International Study on Syncope of Uncertain Etiology (ISSUE) Investigators* Background-In patients with syncope and structural heart disease, syncope is suspected to be attributable to a primary cardiac arrhythmia, but little is known of its mechanism when electrophysiologic study is unremarkable. Methods and Results-We applied an implantable loop recorder in 35 patients with overt heart disease at risk of ventricular arrhythmia, because these were patients with previous myocardial infarction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
2
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(71 citation statements)
references
References 26 publications
7
58
2
4
Order By: Relevance
“…Pezawas et al reported an even greater prevalence of recurrent symptoms (91%) but only 39.4% presented an arrhythmia during the event (mostly bradycardia), without episodes of ventricular tachycardia. 19 We obtained a final diagnosis in 28.2% of the present group, mainly secondary to bradycardia-related events, similar to that reported by ISSUE2 and Entem et al 7,13 One-third of the BBB cohort had a final diagnosis, with a greater rate in those patients without previous EPS, likely because some of the high-risk patients would have been previously diagnosed if the test had been performed. In 2 previous series of patients with syncope, BBB, and negative EPS, the rates of final diagnosis were 36.5% 6 and 45%, 8 mostly brady-…”
Section: Subgroup Analysissupporting
confidence: 84%
See 1 more Smart Citation
“…Pezawas et al reported an even greater prevalence of recurrent symptoms (91%) but only 39.4% presented an arrhythmia during the event (mostly bradycardia), without episodes of ventricular tachycardia. 19 We obtained a final diagnosis in 28.2% of the present group, mainly secondary to bradycardia-related events, similar to that reported by ISSUE2 and Entem et al 7,13 One-third of the BBB cohort had a final diagnosis, with a greater rate in those patients without previous EPS, likely because some of the high-risk patients would have been previously diagnosed if the test had been performed. In 2 previous series of patients with syncope, BBB, and negative EPS, the rates of final diagnosis were 36.5% 6 and 45%, 8 mostly brady-…”
Section: Subgroup Analysissupporting
confidence: 84%
“…Groups were defined according to similar previous studies. [6][7][8] Follow-up data regarding the interpretation of clinical symptoms, recorded electrograms, final diagnosis, and treatment Alzheimer's disease, n=10; non-specific or unknown, n=13). One-third of the patients had SHD (for study purposes, those with BBB or conduction disease were included in the group of BBB for analysis): 132 patients had ischemic heart disease, 24 had dilated cardiomiopathy, 28 had hypertrophic cardiomiopathy, 28 had valvular disease, 9 had congenital disease and 9 had other diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…Structural heart disease and bundle branch block were defined according to the definitions of previously published studies [8,9].…”
Section: Methodsmentioning
confidence: 99%
“…90% of recurrent events showed prolonged asystolic pauses mainly attributable to paroxysmal AV block ( 2 / 3 of patients). In the last subset of 35 patients with mild structural heart disease (mean left ventricular ejection fraction 47 ± 17%) and negative EPS [19], syncope recurred in only 17% and presyncope in 37% over 3-15 months of follow-up, yielding a diagnosis in 40% of patients. Most recurrences were due to bradycardia with long pauses while sustained VT remain unlikely (1 case), stressing that patients with mild structural heart disease and negative EPS show favorable mid-term outcome.…”
Section: Ilr As a Tool To Identify Mechanisms Of Syncopementioning
confidence: 99%
“…Nierop et al [28] reported resolution of symptoms in 17% after ILR implantation. In the different substudies of the ISSUE trial, patients with a mean of ≥2 syncopal episodes during the last 2 years prior to randomisation experienced a decrease in syncope recurrence by a factor of 2 [18], 3 [17] and 5 [19], respectively,in the year following ILR implantation. Moreover, 2 / 3 of ILR-implanted patients included in the ISSUE 2 trial [26], with a median of 4 syncopal events during the last 2 years prior to implantation, did not experience recurrence over a median follow-up of 9 months, highlighting the potential placebo effect of ILR in patients suffering from syncope.…”
Section: Unexpected Therapeutic Properties Of Implantable Devicesmentioning
confidence: 99%